Financial Support Between Spouses: An Analytical Study of the Principles of Kind Treatment and Rights and Duties - Mohammed Hasan, Baidar Mohammed; Wan Ismail, Wan Abdul Fattah; Abdul Rab, Muneer Ali; Hashim, Hasnizam (Al-Daulah : Journal of Criminal Law and State Administration Law, 2025)
This study explores the concept of "financial support between spouses" from a legal and ethical perspective, emphasizing the importance of mutual kindness and the reciprocal rights and duties between spouses. The study aims to analyze how these principles affect family relationships and stability, highlighting that financial support is a fundamental part of mutual kindness. It employs an analytical methodology to review the legal and religious evidence related to spousal maintenance, demonstrating how adherence to financial rights and duties enhances cooperation and integration between spouses. Additionally, it underscores the importance of raising awareness about mutual kindness and support to strengthen family bonds and build a cohesive society. The study concludes that achieving financial support between spouses requires a deep understanding of mutual kindness, rights, and duties, which contributes to family stability.